Optimization of solvent system for chitosan/polylactic acid/nanocellulose nanofibers using needleless electrospinning - Syed, Murtaza Haider; Rahman Khan, Md. Maksudur; Mohd Zahari, Mior Ahmad Khushairi; Hossen Beg, Mohammad Dalour; Norhayati, Abdullah (Wiley, 2024)
Needless electrospinning (NES) is the most advanced and robust method to generate biopolymeric nanofibers. NES overcomes the needle clogging and low throughput issues of conventional needle based electrospinning (ES). However, the issue with all ES techniques is the absence of generalized methods in the literature, and most of the work is being done empirically. The solvent system dictates the feasibility of the ES process, and solvent system based studies can help create more generalized ES methods. The current work provides a systematic approach to fabricating tribiopolymeric nanofibers. NES was used to fabricate chitosan (CS)/polylactic acid (PLA)/nanocellulose (NCC) based nanofibers by optimizing the solvent system using dichloromethane (DCM) and trifluoroacetic acid (TFA). Biopolymeric blend PLA/CS/NCC (10:0.1:0.05 w/v %) in various formulated solvent systems were made and analyzed for their physical properties (sedimentation rate, particle size, viscosity, and surface tension) and subjected to NES. The binary solvent system SS91 (DCM (90):TFA (10) %) showed the lowest sedimentation rate and viscosity while the highest particle size and surface tension, resulting in the beads free nanofibers. The viscosity and surface tension comparison were used to determine a critical point for the feasibility of nanofiber fabrication. Overall, the study showed a systematic approach for fabricating complex tri-biopolymeric nanofibers in future.